Fecal microbiota and inflammatory and antioxidant status of obese and lean dogs, and the effect of caloric restriction - Vecchiato, Carla Giuditta; Golinelli, Stefania; Pinna, Carlo; Pilla, Rachel; Suchodolski, Jan S.; Tvarijonaviciute, Asta; Rubio, Camila Peres; Dorato, Elisa; Delsante, Costanza; Stefanelli, Claudio; Pagani, Elena; Fracassi, Federico; et al. (Frontiers in Microbiology, 2023)
Obesity is the most common nutritional disease in dogs, and is generally managed by caloric restriction. Gut microbiota alteration could represent a predisposing factor for obesity development, which has been associated with a low-grade inflammatory condition and an impaired antioxidant status. Besides, weight loss has been shown to influence the gut microbiota composition and reduce the inflammatory response and oxidative stress. However, these insights in canine obesity have not been fully elucidated. The aim of this study was to assess the differences in serum and inflammatory parameters, antioxidant status, fecal microbiota and bacterial metabolites in 16 obese and 15 lean client-owned dogs and how these parameters in obese may be influenced by caloric restriction. First, for 30 days, all dogs received a high-protein, high-fiber diet in amounts to maintain their body weight; later, obese dogs were fed for 180 days the same diet in restricted amounts to promote weight loss. Before the introduction of the experimental diet (T0), small differences in fecal microbial populations were detected between obese and lean dogs, but bacterial diversity and main bacterial metabolites did not differ. The fecal Dysbiosis Index (DI) was within the reference range (< 0) in most of dogs of both groups. Compared to lean dogs, obese dogs showed higher serum concentrations of acute-phase proteins, total thyroxine (TT4), and antioxidant capacity. Compared to T0, dietary treatment affected the fecal microbiota of obese dogs, decreasing the abundance of Firmicutes and increasing Bacteroides spp. However, these changes did not significantly affect the DI. The caloric restriction failed to exert significative changes on a large scale on bacterial populations. Consequently, the DI, bacterial diversity indices and metabolites were unaffected in obese dogs. Caloric restriction was not associated with a reduction of inflammatory markers or an improvement of the antioxidant status, while an increase of TT4 has been observed. In summary, the present results underline that canine obesity is associated with chronic inflammation. This study highlights that changes on fecal microbiota of obese dogs induced by the characteristics of the diet should be differentiated from those that are the consequence of the reduced energy intake.